2008
DOI: 10.1136/tc.2007.021386
|View full text |Cite
|
Sign up to set email alerts
|

Markers of the denormalisation of smoking and the tobacco industry: Table 1

Abstract: Background:In nations with histories of declining smoking prevalence and comprehensive tobacco control policies, smoking-positive cultures have been severely eroded. Smoking, smokers and the tobacco industry are today routinely depicted in everyday discourse and media representations in a variety of overwhelmingly negative ways. Several authors have invoked Erving Goffman’s notions of stigmatisation to describe the process and impact of this radical transformation, which importantly includes motivating smoking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
185
1
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(198 citation statements)
references
References 44 publications
6
185
1
4
Order By: Relevance
“…At a general level, the pro-non-smoker biases on the self-report measures shown by both groups of non-smokers in the current study support the perception that attitudes toward smokers have become more negative in recent decades (Chapman & Freeman, 2008). Interestingly, bias scores on the IRAP were relatively neutral for both non-smoking groups.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…At a general level, the pro-non-smoker biases on the self-report measures shown by both groups of non-smokers in the current study support the perception that attitudes toward smokers have become more negative in recent decades (Chapman & Freeman, 2008). Interestingly, bias scores on the IRAP were relatively neutral for both non-smoking groups.…”
Section: Discussionsupporting
confidence: 76%
“…Attitudes toward smokers have changed considerably in recent decades (Chapman & Freeman, 2008). The traditional positive characteristics of smokers as glamorous and independent have been replaced with malodorous and selfish stereotypes (Farrimond & Joffe, 2006).…”
Section: Abstract Irap Smokers Attitudes Parental Influencementioning
confidence: 99%
“…3,8 Possible reasons for this increasing trend are a decreasing prevalence of smoking and a decreasing social acceptability of smoking. 5,9 Certain events can potentially trigger sudden increases in support for smoke-free laws. For example, a review of Australian studies showed that population support for smoke-free laws increased significantly after extensive media attention about a court case on disease due to second-hand smoke.…”
mentioning
confidence: 99%
“…Now that tobacco control policy draws in the direction of denormalization of all tobacco consumption, and categorization of tobacco use and users is steered towards marginalization (Chapman & Freeman, 2008), the differences in tobacco user status will be even more affected by their overall lifestyle. This relates also to tobacco consumption as potential signs of different lifestyles: in the contemporary tobacco culture, it seems "better" to smoke a cigar than to smoke rolling tobacco, in the sense that social elites may well allow themselves to be photographed with a cigar, but not with a hand rolled cigarette.…”
Section: Distinction Differences Between Various Tobacco Products Andmentioning
confidence: 99%